Pembelajaran Berbasis Reciprocal Teaching untuk Meningkatkan Kemampuan Koneksi Matematis Mahasiswa - Tika Dwi Nopriyanti; Allen Marga Retta (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2020)
Mathematical ability which is very important for students, especially prospective educators, is connection mathematical ability (CMA). This is because students can apply mathematics learning in daily life or with other sciences such as economics, physics, and others. Therefore, researchers wanted to improve the CMA of students with reciprocal teaching (RT) based learning strategies. The quasi-experimental method was used in this study with a non-equivalent pre-test and post-test control group design with 43 students in second semester Mathematics Education of a University in Palembang Indonesia as the subject of this study. The subjects of this study consisted of 2 classes, namely the experimental class and the control class. Data analysis in this research used the final test At the end of the study, n-gain was obtained for classes with RT-based learning strategies of 0.43 while conventional classes obtained n-gain of 0.32, which means that RT-based learning strategies can improve student mathematical connection ability.